Effects of Teacher Engagement on Students’ Achievement in an Online English as a Foreign Language Classroom: The Mediating Role of Autonomous Motivation and Positive Emotions - Wang, Jianhua; Zhang, Xi; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
As an important factor promoting students’ learning behavior and achievement, teacher engagement has been largely neglected in the research literature on English as a foreign language (EFL) and applied linguistics. Moreover, the few studies have focused more on conventional classrooms rather than online learning contexts and failed to reveal how teacher engagement in the online foreign language classroom affected students’ achievement. The present study assessed 546 university students in China using self-report questionnaires to examine the relationship between teacher engagement and students’ achievement in an online EFL course over an 18-week semester, taking into account the possible mediating effects of autonomous motivation and positive academic emotions. The results showed that teacher engagement exerted a direct and positive impact on students’ English achievement. Students’ autonomous motivation and enjoyment mediated the association between teacher engagement and English achievement, but the mediating effects of relief were not significant. Additionally, teacher engagement affected students’ English achievement through the chain mediation of autonomous motivation and positive academic emotions (enjoyment and relief). Relief displayed a smaller effect on students’ English achievement than enjoyment did. These findings elucidate the impact of teacher engagement on students’ English achievement in the online environment and support the utility of self-determination theory and control-value theory in explaining foreign language learning. Directions for future research and implications for education are also presented.